2022
DOI: 10.37394/23207.2022.19.112
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Knowing the Profile of Online Shoppers on Online Shopping: Evidence From City of Berat, Albania

Abstract: Electronic commerce is a type of business in which all transactions are carried out online and the seller and buyer do not meet in person, as in traditional commerce. E-commerce has been steadily increasing over the last decade, and it is now a popular method of shopping in many parts of the globe. As more businesses are switching to online sales, their sales strategies are adapting to the needs of their online customers, including customers demographic and psychographic characteristics. Therefore, in an effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The literature shows conflicting results related to the influence of gender on e-shopping. Some researchers found that gender significantly affects e-shopping [9,[23][24][25][26][27][28], while others found that gender is insignificant [29][30][31][32][33][34][35]. Some research papers showed that women engage in e-shopping more than men [9,12,24].…”
Section: Determinants Of E-shoppingmentioning
confidence: 99%
“…The literature shows conflicting results related to the influence of gender on e-shopping. Some researchers found that gender significantly affects e-shopping [9,[23][24][25][26][27][28], while others found that gender is insignificant [29][30][31][32][33][34][35]. Some research papers showed that women engage in e-shopping more than men [9,12,24].…”
Section: Determinants Of E-shoppingmentioning
confidence: 99%
“…Many children from rural areas do not attend school. When compared to other nations, the quality of education is among the lowest, and the expense of education is likewise among the lowest (Buhaljoti, 2016). The study has two goals: first, to support the country's National Pre-University Education Strategy, and second, to ensure that the country meets European Union membership requirements.…”
Section: Optimal Relation Between Education and Economymentioning
confidence: 99%
“…Several studies on long-term growth in poor nations conducted by development analysts looked at the relationship between education and economic development. Individual and group production are important markers of human capital, according to the results mentioned above (Buhaljoti, 2016). In academic literature, human capital is often regarded as an essential indicator of individual and group productivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations